KOMUNIKASI DIGITAL DAN PERUBAHAN SOSIAL - Boestam, Ambia B; Derivanti, Azizah Des (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The development of digital technology is currently changing the habits that exist in society. The social changes that occur are caused by rapid technological advances and cannot be avoided by the community. Technological advances that occur in various aspects require people to change their behavior patterns, including social interaction. It is realized that changes in interactions that occur in society change in various aspects such as entertainment, information, education, to the economy where these are interrelated. Based on this, the impact of digital technology is very large, not only changing social interactions, the economy, even government policies can be changed to adapt to current technological developments. Digital communication is used as a public medium to criticize the existing rulers. Digital communication is no longer just a forum for community interaction, providing digital communication with a broader perspective. Therefore, this paper aims to identify and describe the phenomenon of digital communication on social changes that occur in society